Produtividade e fitodisponibilidade de nutrientes e metais pesados tóxicos (Cd, Cr e Pb) na tifton 85 fertilizada com dejetos provenientes da suinocultura - Zenatti, Ricardo (2011)
The aim of this work was evaluate the effect of the application of swine manure increasing doses in the production and the content of nutrients and toxic heavy metals in two cuts of the forage Tifton 85 (Cynodon dactylon) grown in two different soil textures. The experiments were carried out in greenhouse using an Rhodustults (PVe) of sand texture, and an Haplustox (LVe) of clay texture. It was used a completely randomized design (CRD), 2x4 factorial with treatments consisting by two sources of the organic fertilizer based on swine manure (in nature and biofertilizer) and four doses for each source, with four replications. In the first cut, for the PVe, the two sources of fertilizer influenced the vegetable content of P and Mn and the doses influenced the N, P, K, Cu and Zn content. To the LVe, the sources influenced the vegetable content of Mg and the doses influenced on N, P, K, Mg, Cu, Fe levels. Yet observed in the first cut that the use of biofertilizer provided higher accumulation of Cr in the tissue plant when compared to the use of in nature manure. In the second cut, for the LVe, the sources influenced the vegetable contents of the elements P, Fe, Mn and Cu, and the doses influenced the N, P, K, Fe, Mn and Cu levels, and for the LVe, the sources influenced the vegetable content of the elements P and Cu, and the doses influenced the N, P, K, Fe, Mn, Cu and Zn levels. For the toxic heavy metals studied, the Pb content in the LVe was higher compared to the PVe, and the levels values were above the value assigned by CETESB (17 mg kg-1) as an indicator of soil quality. It was concluded that the application of in nature manure provided highest production of Tifton 85 when compared with the use of biofertilizers. The doses influenced on N, P, K and Cu in plant tissue and the levels of toxic heavy metals Cr and Pb in both cultivation soils